If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+10=18+6x-12/2
We move all terms to the left:
2x+10-(18+6x-12/2)=0
We add all the numbers together, and all the variables
2x-(6x+12)+10=0
We get rid of parentheses
2x-6x-12+10=0
We add all the numbers together, and all the variables
-4x-2=0
We move all terms containing x to the left, all other terms to the right
-4x=2
x=2/-4
x=-1/2
| 6(x-8)+15x=-35 | | 14+2(5x-3)=18 | | .04x-125=375 | | t^2-9+18=0 | | 2+6=8-4x/6 | | 8x-6(3-x)=10 | | 162=-2x+4(3x+13) | | 1/2(x+3)=1/3(3x+6) | | 4-3p=16 | | t²-9+18=0 | | 15x+(-3)=-11+13x | | 4-3p=14 | | 1=1/4x+5+3 | | 162=-2x+4(3x+13 | | 7(v+2)-3v=2(2v+3)-9 | | t*2-9+18=0 | | 20=y=8 | | 3=q2 | | 0=-16t+8t+24 | | 57=15+6y | | -4x+2(5x+2)=52 | | 0.7x+4=340 | | 12x(2)=6(20) | | W=3x15/8 | | 24+2x=3x+2(12) | | 12^2x+3=144 | | 4b=10b–84 | | -28=5u+7 | | 7t+27=5t+47 | | 36-8x=7x+2 | | 6y=5y+12 | | 98=6x+4(3x+2) |